Dermoscopy is a new diagnostic tool in diagnosis of common hypopigmented macular disease: A descriptive study (Dermatology Reports, 2018)
One of the most frequent complaints in dermatology clinics is the eruption of hypopigmented patchy skin lesions. The aim of the study was to investigate the utility of dermoscopy in common hypopigmented macular diseases. Patients with the followings diseases were examined by dermoscopy: vitiligo, pityriasis alba, nevus depigmentosus, achromic pityriasis versicolor, idiopathic guttate hypomelanosis, and extragenital guttate lichen sclerosus. This study showed that these hypopigmented macular diseases might display specific dermoscopic features. In vitiligo, the mean dermoscopic features were the presence of a diffuse white glow with perifollicular pigment, perilesional hyperpigmentation, leukotrichia and the pigmentary network. In idiopathic guttate hypomelanosis, the characteristic features were the presence of multiple, shiny, scaly macules with welland ill-defined edges borders that coalesced into polycyclic macules. For nevus depigmentosus, the mean features were hypopigmented patches with irregular border with a faint reticular network. For pityriasis alba, the fairly ill-demarcated hypopigmented macules with fine scales were the mean feature. In lichen sclerosus, there were white structureless areas, perilesional erythematous halo, follicular plugging and white chrysalis like structures. Dermoscopy of achromic pityriasis versicolor showed a fairly demarcated white area with fine scales localized in the skin creases.